Pengaruh Sistem Pengendalian Internal, Budaya Organisasi Dan Kompetensi Sumber Daya Manusia Terhadap Pencegahan Fraud Dengan Good Corporate Governance Sebagai Variabel Intervening - Ni Putu Agustina Widyawati; Edy Sujana; I Putu Gede Diatmika (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2023)
ABSTRACT This study aims to examine and analyze the effect of the internal control system, organizational culture and human resource competence on fraud prevention with good corporate governance as an intervening variable. The data collection method used a survey method using a questionnaire. The population of this research is BUMDes Management in Buleleng Regency, which is 761 people. The sampling technique used was purposive sampling with criteria for BUMDes management who served as chairman and treasurer of BUMDes. Based on these criteria, a sample of 252 people from 126 BUMDes in Buleleng Regency was obtained. The data analysis method used in this research is to use the help of Smart PLS software version 3.0. The results showed that the internal control system, organizational culture, and human resource competence had a positive and significant effect on good corporate governance. Internal control system and human resource competence have a positive and insignificant effect on fraud prevention, while organizational culture and good corporate governance have a positive and significant effect on fraud prevention. Internal control system, organizational culture and competence of human resources through Good Corporate Governance have a positive and significant effect on fraud prevention. Keywords: internal control system, organizational culture, human resource competence, fraud prevention, good corporate governance